Silybin is metabolized by cytochrome P450 2C8 in vitro - Jancová, Petra; Anzenbacherová, Eva; Papousková, Barbora; Lemr, Karel; Luzná, Pavla; Veinlichová, Alena; Anzenbacher, Pavel; Simánek, Vilím (Drug metabolism and disposition: the biological fate of chemicals, 2007)
Silybin (a flavonolignan, the main component of silymarin, an extract from the seeds of Silybum marianum) has been used to date mostly as a hepatoprotectant. However, it also has other interesting activities, e.g., anticancer and hypocholesterolemic effects. It is also known that silybin can inhibit the activities of the cytochrome P450 (P450) enzymes. In this study, a weak interaction of silybin with human microsomal CYP2E1, 2A6, 2B6, 2C19, and 2D6 (IC(50) > or = 250 microM) was found; a moderate inhibition was observed for CYP1A2 and 2C8. The most prominent inhibition effect was found with CYP3A4 and CYP2C9 (IC(50) < or = 50 microM). Using mass spectometry detection, production of O-demethylated (the main metabolite) as well as hydroxylated derivatives of silybin formed by P450 enzymes was detected. The effect of different P450 inhibitors on the formation of O-demethylated product was also studied. In particular, a relatively specific inhibitor of CYP2C8 (quercetin) markedly inhibited the formation of this metabolite. With the help of recombinant enzymes (bactosomes), it was confirmed that the CYP2C8 enzyme is responsible for the reaction leading to O-demethylated silybin.
Keywords: inhibitory cytochromu P450 CYP1A2; Cytochrome P-450 CYP3A; Catalysis; quercetin; Antioxidants; cytochrom P450 CYP2C8; Escherichia coli; katalýza; oxid uhelnatý; vysokoúčinná kapalinová chromatografie; Enzyme Inhibitors; Molecular Structure; lidé; rekombinantní proteiny; Recombinant Proteins; cytochrom P-450 CYP3A; Cytochrome P-450 CYP1A2 Inhibitors; Cytochrome P-450 CYP2C8; jaterní mikrozomy; silibinin; inhibitory cytochromu P450; molekulární struktura; Chromatography, High Pressure Liquid; Cytochrome P-450 CYP1A2; silymarin; inhibitory enzymů; Aryl Hydrocarbon Hydroxylases; systém (enzymů) cytochromů P-450; antioxidancia; cytochrom P450 CYP2C9; Microsomes, Liver; Silybin; Quercetin; cytochrom P-450 CYP1A2; Cytochrome P-450 Enzyme Inhibitors; Carbon Monoxide; Cytochrome P-450 CYP2C9; Cytochrome P-450 Enzyme System; aromatické hydroxylasy; Silymarin; Humans